CIDE and elasticity oscillation on the ethanol and gasoline market: Brazilian taxation policy under discussion - Mario Antonio Margarido; Gesmar Rosa dos Santos; Carlos Eduardo Freitas Vian; Pery Francisco Assis Shikida; Bárbara Françoise Cardoso Bauermann (Italian Review of Agricultural Economics (REA), 2020)
The aim of this paper is to identify the path of the gasoline price elasticity, ethanol price elasticity, ethanol-gasoline cross-price elasticity and the gasoline-ethanol cross-price elasticity for the flex-fuel vehicle market, as well as to discuss the taxation policies impact of the Economic Domain Intervention Contribution (CIDE) on the ethanol and gasoline markets. Therefore, it was used the Structural Methodology model, as well as official data from 2003 to 2007. The results show great power of influence of the tax on the gasoline's price and on the costumer's choice between ethanol or gasoline. Thus, the CIDE is one of the most important reasons for ethanol consume, contributing to an effective reduction in the green house gases and atmospheric pollutants emissions.
Keywords: Q42; Q48; 330; Brazilian taxation policy; price elasticity; ethanol; gasoline; consumer's choice